2018
DOI: 10.1111/cod.13079
|View full text |Cite
|
Sign up to set email alerts
|

Contact allergy in Danish children: Current trends

Abstract: Allergic contact dermatitis continues to be a common disease in children, and is even significantly increasing for some allergens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
44
2
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 63 publications
5
44
2
1
Order By: Relevance
“…Based on the results of our study, the prevalence of contact allergy in atopic children is comparable to that noted in non-atopic children (p = 0,2958, odds ratio 0,75). Our results are not in line with a recent systematic review [13] showing that the risk of developing contact allergy in children with AD was less than those who were not atopic, while are in agreement with a recent study based on patch test data of 1573 children from the Danish National Database of Contact allergies [14]. As noted by these authors, the sensitization rates reported considerably varied, as did the studies regarding size, study design, allergens used for patch testing, the patch test methodology, age and sex distribution, and criteria for atopic dermatitis, which make difficult to draw any strong conclusion regarding the relationship between AD and contact allergy.…”
Section: Discussioncontrasting
confidence: 56%
“…Based on the results of our study, the prevalence of contact allergy in atopic children is comparable to that noted in non-atopic children (p = 0,2958, odds ratio 0,75). Our results are not in line with a recent systematic review [13] showing that the risk of developing contact allergy in children with AD was less than those who were not atopic, while are in agreement with a recent study based on patch test data of 1573 children from the Danish National Database of Contact allergies [14]. As noted by these authors, the sensitization rates reported considerably varied, as did the studies regarding size, study design, allergens used for patch testing, the patch test methodology, age and sex distribution, and criteria for atopic dermatitis, which make difficult to draw any strong conclusion regarding the relationship between AD and contact allergy.…”
Section: Discussioncontrasting
confidence: 56%
“…The prevalences are approximately 8% to 19% in adults and 8% to 10% in children and adolescents in the general population, with a strong predominance in women as compared with men (4‐10 times) and in girls as compared with boys . In dermatitis patients, the prevalence is higher (adults, 12%‐25%; children, 5%‐30%) . Nickel allergy has been less investigated outside of Europe, although persistently high prevalences have been observed in Asia and North America .…”
Section: Epidemiology Of Nickel Allergymentioning
confidence: 99%
“…8 In dermatitis patients, the prevalence is higher (adults, 12%-25%; children, 5%-30%). [9][10][11][12][13] Nickel allergy has been less investigated outside of Europe, although persistently high prevalences have been observed in Asia and North America. [14][15][16][17][18][19][20] A higher prevalence of nickel allergy in individuals with atopic dermatitis has been shown in some studies, whereas others have found negative associations.…”
mentioning
confidence: 99%
“…Contact allergy is common and increasing in children, and may have important repercussions on quality of life and social relationships. 3 Contact allergy in children is thought to be caused by a high exposure to allergens at a younger age, especially in case of breakdown of the skin barrier, as occurs in AD. However, the relationship between contact allergy and AD is still controversial, with some studies reporting a reduced sensitization among patients with AD compared with nonatopics.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Regarding Cr, the most common sources of exposure are thought to be leather footwear, followed by toy make-up and mobile phones. 3 From May 2015, the level of Cr(VI) in leather articles placed on the markets of European countries that come into contact with the skin has been restricted to <3 ppm. 2 However, a reduction in the amount of Cr exposure remains an important health consideration.…”
Section: Discussionmentioning
confidence: 99%